Effect of Glycerol Concentration and Gelatinization Temperature on Beneng Taro (Xanthosoma undipes K. Koch) Starch/PVA Bioplastic Films Prepared by Solvent Casting - Mella Herdini; Evi Triwulandari; Wardalia Wardalia (World Chemical Engineering Journal, 2026)
Bioplastics based on Beneng taro (Xanthosoma undipes K. Koch) starch were prepared using the solvent casting method with glycerol as a plasticizer and polyvinyl alcohol (PVA) as an additional polymer. This study aimed to evaluate the effects of glycerol concentration and gelatinization temperature on the mechanical, chemical, and thermal properties of starch-based bioplastic films. Films were prepared at starch:glycerol ratios of 60:40, 70:30, and 80:20 (w/w), with gelatinization temperatures of 75, 80, 85, and 90 °C. The amylose content of Beneng taro starch was 11%. Increasing glycerol concentration increased elongation at break from 10.30% to 29.04%, but decreased tensile strength from 5.13 MPa to 0.84 MPa. FTIR analysis indicated the presence of characteristic O–H, C–H, and C–O functional groups, suggesting hydrogen-bonding interactions among starch, glycerol, and PVA without the formation of new functional groups. DSC analysis showed melting temperatures in the range of 82–91 °C, with the highest thermal stability observed at a gelatinization temperature of 80 °C. These results indicate that glycerol concentration and gelatinization temperature strongly influence the flexibility, mechanical strength, and thermal behavior of Beneng taro starch-based bioplastic films.